Multi-omics analysis reveals genes and metabolites involved in Bifidobacterium pseudocatenulatum biofilm formation - Zhang, Ting; Liu, Zongmin; Wang, Hongchao; Zhang, Hao; Li, Haitao; Lu, Wenwei; Zhu, Jinlin (Frontiers in Microbiology, 2023)
Bacterial biofilm is an emerging form of life that involves cell populations living embedded in a self-produced matrix of extracellular polymeric substances (EPS). Currently, little is known about the molecular mechanisms of Bifidobacterium biofilm formation. We used the Bifidobacterium biofilm fermentation system to preparation of biofilms on wheat fibers, and multi-omics analysis of both B. pseudocatenulatum biofilms and planktonic cells were performed to identify genes and metabolites involved in biofilm formation. The average diameter of wheat fibers was around 50 µm, while the diameter of particle in wheat fibers culture of B. pseudocatenulatum was over 260 µm at 22 h with 78.96% biofilm formation rate (BR), and the field emission scanning electron microscopy (FESEM) results showed that biofilm cells on the surface of wheat fibers secreted EPS. Transcriptomic analysis indicated that genes associated with stress response (groS, mntH, nth, pdtaR, pstA, pstC, radA, rbpA, whiB, ybjG), quorum sensing (dppC, livM, luxS, sapF), polysaccharide metabolic process (rfbX, galE, zwf, opcA, glgC, glgP, gtfA) may be involved in biofilm formation. In addition, seventeen weighted gene co-expression network analysis (WGCNA) modules were identified and two of them positively correlated to BR. Metabolomic analysis indicated that amino acids and amides; organic acids, alcohols and esters; and sugar (trehalose-6-phosphate, uridine diphosphategalactose, uridine diphosphate-N-acetylglucosamine) were main metabolites during biofilm formation. These results indicate that stress response, quorum sensing (QS), and EPS production are essential during B. pseudocatenulatum biofilm formation.